Work from home (WFH) and productivity: An exploratory study among government servant in Tawau Sabah - Roslinah Mahmud; Khairul Hanim Pazim; Rostika Petrus Boroh; Noor Fzlinda Fabeil; Beatrice Lim Fui Yee; Kasim Mansur (Universiti Malaysia Sabah, 2021)
The main objective of this study is to describe the relationship between work from home and work productivity among government servant in Tawau Sabah, Malaysia to WFH based on the survey during a post crisis. COVID-19 pandemic has led to dramatic changes like work and how work can be performed. A flexible work arrangement allows workers to work from home (WFH) as a form of work continuity in times of crisis. WFH is generally applied to employers and workers during the COVID-19 pandemic. This is one of the government's steps to reduce the transmission of coronavirus disease by restricting physical interaction. This study used primary data based on a structured questionnaire to find out the impact WFH to work productivity based on the perception of government servant in Tawau, Sabah. The findings revealed that most of the respondent believe that their productivity can be increased during WFH applied (MCO phase 1 or after Post-Covid19). The result also found the demography factors such as comfortability, gender, age, and number of children have significant relationship with work productivity during work from home (WFH). The findings add to the limited literature on the demographic factors influence WFH work productivity during post crisis. The government should take numerous steps to encourage workers stay productive with concerning to the factors that influence WFH productivity to continue work in a new norm after Covid-19.